Agricultural research:Promoting interactivity - Woodard, Josh; Otieno Omolo, Dominic (Technical Centre for Agricultural and Rural Cooperation, 2013)
ICTs can help researchers to interact with farmers. The challenge lies in finding a way of integrating traditional and new communication technologies to send agricultural and market information to farmers